THE ROLE OF VALUE CO-CREATION IN THE APPLICATION OF SERVICE-DOMINANT LOGIC THEORY IN ODOO INNOVATION MARKETING PROGRAMS - Afaf, Irfan; Marsasi, Endy Gunanto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Researchers examined a company engaged in software development, providing several applications or software to help run the company. This study aims to propose a marketing program to evaluate the features contained in the company's products. This study used a descriptive qualitative method with data collection through observation, in-depth interviews, company secondary data, and documentation collection. This research resulted in an analysis of the proposed Odoo Innovation program, namely adding features to the Odoo application. The theory of Service-Dominant Logic assists the proposed program with the concept of Value Creation to assist companies in increasing sales. Service-dominant logic, with the idea of Value Co-Creation, can help the company's marketing develop and become a strength for PT Panemu Solusi Industri.